Socio-Demographics Characteristics on Investment Objectives of Individual Investors: Empirical Study in Indonesia (STIE Malangkucecwara, 2019)
Every investor has a unique choice of investment based on customized needs and goals. Each investment has its characteristics. This study investigates the association between socio-demographic characteristics of individual investors and the objectives of the investments. Employing Pearson’s chi-square test with 125 respondents from securities companies in Indonesia, we suggest that the decision of investors in investing their money depends on the association between sociodemographic characteristics and the characteristics of investments' goals. The results of this study can benefit both individual investors and securities firms. For individual investors, this study can be a guideline for them to make an investment decision by considering an investment objective that suits them the most. While for the securities companies, they can market their products to investors appropriately by looking into the demographic factors of the investors and indirectly know the investors’ investments preference. More, the government needs to enhance the infrastructure of the financial sector in order to increase individuals participation in the sector